2002
DOI: 10.1073/pnas.152120699
|View full text |Cite
|
Sign up to set email alerts
|

The CcmE protein of the c -type cytochrome biogenesis system: Unusual in vitro heme incorporation into apo-CcmE and transfer from holo-CcmE to apocytochrome

Abstract: Three key steps of cytochrome c biogenesis in many Gram-negative bacteria, the uptake of heme by the heme chaperone CcmE, the covalent attachment of heme to CcmE, and its subsequent release from CcmE to an apocytochrome c, have been achieved in vitro. apo-CcmE from Escherichia coli preferentially bound to ferric, with high affinity (K d , 200 nM), rather than ferrous heme. The preference for ferric heme was confirmed by competition with 8-anilino-1-naphthalenesulfonate, which bound to a hydrophobic pocket in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 45 publications
7
104
2
Order By: Relevance
“…Purified CcmE produced under the conditions described contained a substantial amount of apo-protein; usually about 20% of the protein contained covalently attached heme as determined by comparing the ratio of the absorbance value at 280 nm (apoprotein ϩ holo-protein) with the intensity of the Soret band (holo-protein). The co-production of large amounts of apoprotein with holo-protein has been observed previously with CcmE (6,11). Only the apo-forms of the proteins produced were observed in the mass spectra; the heme-containing form does not appear in the spectra under these conditions.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Purified CcmE produced under the conditions described contained a substantial amount of apo-protein; usually about 20% of the protein contained covalently attached heme as determined by comparing the ratio of the absorbance value at 280 nm (apoprotein ϩ holo-protein) with the intensity of the Soret band (holo-protein). The co-production of large amounts of apoprotein with holo-protein has been observed previously with CcmE (6,11). Only the apo-forms of the proteins produced were observed in the mass spectra; the heme-containing form does not appear in the spectra under these conditions.…”
Section: Resultssupporting
confidence: 65%
“…Cultures were first grown to mid-log phase at 37°C following inoculation and then induced with 1 mM isopropyl-thio-␤-D-galactopyranoside and grown overnight at 28°C. Proteins were purified as described previously (11). Thrombin digestion was performed using a CleanCleave kit (Sigma) according to the manufacturer's instructions, and the uncleaved protein was separated from the cleaved protein by reapplying the protein mixture to a Ni 2ϩ -chelating Sepharose column.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in phylogenetic analysis, the CcmA family cluster belongs to the exporter sub family ABC-A2, which contains proteins having the ABC modules not fused to TMD (46). An electron donor, essential to maintain the heme iron in a reduced state after its transfer to CcmE, could be a possible substrate for the system I ABC transporter and essential for the release of heme to apocytochrome c. Indeed, in vitro and in vivo approaches showed that heme iron needs to be reduced for the covalent linkage to occur (47)(48)(49). In yeast mitochondria, a flavin-linked electron transfer was postulated for heme lyase reaction (49), and Cyc2p a flavoprotein was proposed to reduce heme iron before its attachment to apocytochrome c by cytochrome c heme lyase (50).…”
Section: Discussionmentioning
confidence: 99%